2015
DOI: 10.1021/acs.cgd.5b00216
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Quality, Growth Kinetics, and Photocatalysis of ZnO Nanowalls Prepared by Chemical Bath Deposition

Abstract: ZnO nanowalls (NWLs) represent a non-toxic, abundant and porous material, with promising applications in sensing and photocatalysis. They can be grown by low-cost solution methods on Al (covered) substrates -Al(OH) 4 -generated in situ is assumed to be responsible for engendering the NWL morphology. Here, we grew ZnO NWLs by chemical bath deposition (at 70-95°C).The roles of pH, concentration of Al(OH) 4 -, and growth time on the thickness and quality of NWL film were experimentally investigated and the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…[23,24]. The growth of all these ZnO nanostructures is known to follow a simple "nucleation and growth"…”
Section: Microstructure Of Zno Nanosheets and Zno-fluoropolymer Compomentioning
confidence: 99%
See 4 more Smart Citations
“…[23,24]. The growth of all these ZnO nanostructures is known to follow a simple "nucleation and growth"…”
Section: Microstructure Of Zno Nanosheets and Zno-fluoropolymer Compomentioning
confidence: 99%
“…substrates alongside HMTA and zinc precursor has been shown to be crucial [24]. It has been previously shown that the binding of Al(OH) 4 -to the Zn 2+ terminated surface is essential for suppressing the ZnO growth along the (0001) direction and promoting lateral growth of ZnO nanosheets [24].…”
Section: Microstructure Of Zno Nanosheets and Zno-fluoropolymer Compomentioning
confidence: 99%
See 3 more Smart Citations